Spontaneous pattern transfer and selective growth of graphene on a Cu foil. (February 2015) - Lee, Sanghwa; Jue, Miyeon; Kim, Chinkyo
Abstract: When a 25-μm-thick Cu foil placed on top of a selectively FeCl3 -coated quartz substrate was heated inside a furnace at 1000 °C in a H2 /Ar atmosphere, a FeCl3 mask pattern on a quartz was spontaneously transferred to the front side of the Cu foil. Due to this spontaneous pattern transfer, a subsequent heating process in H2 /Ar/CH4 atmosphere led to selective growth of graphene on the front side of the Cu foil. Surface analysis revealed that a spontaneously transferred mask on a Cu foil was made of SiO2, and Si in SiO2 was found to be from the quartz substrate. Computational simulation of surface diffusion of Si on a Cu foil was consistent with experimentally observed microstructures of spontaneously transferred pattern boundaries, which suggests that oxidation of diffused Si atoms, which originated from the FeCl3 -coated region of a quartz, on the Cu surface was the crucial mechanism of the spontaneous pattern transfer.